Integration of Islamic Values with Environmental Ethics in Pesantren Education: A Case Study at Darularafah Raya Pesantren - Syukri, Syukri; Amir, Sulaiman Muhammad; Fitriani, Fitriani; Pane, Sarmalina (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2024)
Purpose – This study aims to discuss the paradigm of environmental ethics education in pesantren, focusing on the integration of Islamic values and environmental awareness. The importance of this research lies in understanding how pesantren, as Islamic educational institutions, contribute to environmental sustainability through their teachings and practices, while addressing the empirical evidence gap regarding the effectiveness of such education. Design/methods/approach – Utilizing a qualitative case study approach, this research explores the Darularafah Raya Pesantren in Deli Serdang, North Sumatra. Data were collected through participatory observations, in-depth interviews with key stakeholders (including teachers, students, and pesantren administrators), and document analysis of curriculum materials and official records. Thematic analysis was employed to identify and analyze key themes related to the integration of Islamic values and environmental ethics. Findings – The study reveals a holistic approach at Darularafah Raya Pesantren, where Islamic teachings are closely integrated with environmental ethics. Key findings include specialized training for teachers to impart environmental values in daily lessons, extracurricular programs supporting environmental awareness, and the adoption of sustainable practices such as waste management and renewable energy use. The pesantren curriculum emphasizes concepts such as khalifah (stewardship) and amanah (responsibility), which are taught alongside practical environmental conservation activities. Research implications – These findings highlight the potential of pesantren as models for other Islamic educational institutions in promoting environmental sustainability. By integrating Islamic values with environmental ethics, pesantren can shape individuals who are both spiritually and environmentally conscious. Future research should focus on comparative studies across different pesantren and longitudinal studies to assess long-term impacts